Les Formations ouvertes à distance (FOAD) : quelle contribution au développement de professionnels qualifiés en Afrique ? - Thierry Karsenti; Simon Collin (Université de Provence, 2010)
This article presents the results of a three-year (2007-2010) longitudinal study on open and distance learning (ODL) offered by the Agence Universitaire de la Francophonie (AUF). We provide an overview of ODL in Africa in an attempt to gain a deeper understanding of its effectiveness in developing African professionals. We focus on the results of the second study year, obtained from statistical and qualitative analyses of the online questionnaires filled out by 626 respondents. The results indicate that learners are motivated to take ODL courses in order to continuously develop their professional competencies. Although the participants encountered various problems (in terms of technology, pedagogy and infrastructure), they nevertheless expressed high satisfaction with ODL and reported that they gained real benefits. In light of these results, we draw some conclusions on the contributions and limitations of ODL in Africa today.